Retinochoroiditis Toxoplasmika Kongenital yang Menyebabkan Juling - Nunuk Maria Ulfah, Suhardjo, Nunuk Maria Ulfah, Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
Four cases of 1- to 12-year old children with strabismus were reported. In all cases no abnormality of both the motoric and the refractive media of the eye were found. On the other hand, funduscopic examination revealed macular and retinal lesions in the form of rosette pigmentation and pseudocoloboma which were suggestive of the existence of congenital toxoplasmic retinochoroiditis.This suggestion was confirmed to be true with serologic examination for Taxopla,sma. It was thought that the squintness was secondary to the congenital toxoplasmic retinochoroiditis and possible mechanism was discussed.Key Words: toxoplasmic retinochoroiditis Ã¢â¬â disturbance of binocular vision Ã¢â¬â strabismus Ã¢â¬â rosette pigmentation Ã¢â¬â latex agglutination